The role of the family physician in the quality of diabetic care - Czech, Anna (Przewodnik Lekarza/Guide for GPs, 2009)
Due to the epidemic character of diabetes mellitus type 2 and prediabetic state the prevention and long-term management of these diseases are now one of the essential tasks of family or primary care physicians. Their activities shape the quality of diabetes mellitus care in general. In this particular matter an innovative approach is necessary – it is the subject of the presented discussion.